Author Productivity and Lotka’s Law in Nursing Research Output as Mirrored in the Nursing Journal of India, 2010-2024 - Koley, Susanta (Journal of Data Science, Informetrics, and Citation Studies)
Lotka’s law is one of the empirical laws in bibliometric research. Present study analysis 661 research articles (excluding 3 Hindi versions) from 15 volumes (2010-2024) of the Nursing Journal of India which were produced by 1412 authors. The study highlights trends in research output distribution, authorship patterns, collaboration degrees, collaborative indices, year wise author productivity, and identifies leading contributors. In 2015, 47 papers were produced by 80 authors, which resulted in the highest author productivity at 0.58 papers per author. Overall productivity per author for the entire period is calculated at 0.47, with a total author productivity 1412 for 661 outputs, reflecting a healthy contribution of authors throughout the years. The highest number of papers belongs to single-authored, with a total of 321 papers produced by 321 individual authors. There are 1411 personal authors and 1 corporate author. Among leading collaborators, Latha Venkatesan emerged as the most prolific author, having published 11 papers during the period. In all, DC and CI for the data set of this study come out to be 0.5143 and 2.1361 respectively. This study examines validation of Lotka’s Law considering author productivity for the data set in nursing research output. It explores variations in Lotka’s Law using the Lotka’s exponent value of n=3.4 (calculated through Sen’s method) and n=2 (for the ideal case, as per Lotka’s method). A significant gap was observed between the expected [Y(E)] and observed values [Y(O)] with n=2, showing that the difference of 1.4 between the two values indicates a noticeable divergence. The analysis concludes that Lotka’s Law holds with an exponent of n=3.4 in nursing, contrasting with the lower exponent of n=2 used in exact sciences. This suggests that nursing research has fewer authors contributing multiple articles, which leads to a higher n value compared to the exact sciences. Thus, the observed distance highlights that Lotka's Law does not align well with the nursing literature for this dataset when applying n=2 (the ideal value according to Lotka).
Keywords: Author productivity; Bibliometric study; Lotka’s exponent; Lotka’s Law; Nursing research; Sen’s calculation method; The Nursing Journal of India (NJI); Trained Nurses’ Association of India (TNAI).